Accessible to all universities - Stupp Kupiec, Roxana (2011)
This paper aims to raise awareness aboutfactors that affect the collective construction ofuniversities willing to innovate and transform theirideology, policies, curriculum, student services, physical and administrative infrastructure andcommunication and information strategies, under the paradigm of accessibility in the environment. Reference is made to international and national legal framework that guidesactions to be planned and implemented inHigher Education institutions.Universities in building accessible for all requires a change in curriculum design. It discusses concepts such as flexibility in access to training and curricula to respondto the educational needs of all students.To promote these transformations are proposed principles and practices such as interdisciplinarity andinclusion of disability issues in all races. In addition, examples of implementation in different areas of professional profile, in traininguniversity teaching and outreach activities, student life and research. Student in the field, describes some services and processesdeveloped at the University of Costa Rica.